Assessment of the coordination of low-carbon development and socio-economic development based on a comprehensive model: A case study of Anhui Province (China) - Xing, Qinfeng; Yang, Ziwei (Frontiers in Public Health, 2022)
With the proposal of “double carbon” goal, it is urgent to make the coordination of low-carbon development and socio-economic development. So an evaluation index system based on four dimensions of resource environmental endowment, energy environmental endowment, economic development endowment and social development endowment is constructed. And then, comprehensive development assessment model, coupling coordination degree model, synergistic degree model and GM(1,1) model were used for econometric analysis of relevant data from 2011 to 2020 in Anhui Province (China). The results show: 1) Low-carbon development lagged behind socio-economic development; 2) Low-carbon development and socio-economic were mutually beneficial; 3) The coordinated level of low-carbon development and socio-economic development in Anhui province were continuously improved, and the ordered structure will be realized in 2024 and 2029 respectively. This study deepens the theoretical cognition of low-carbon development, and puts forward the following countermeasures based on the research results: Highlighting the strategic guidance of sustainable development; Developing new regulatory mechanisms for low-carbon development; Innovating the science and technology to resolve major development crises.